Vertical transmission rates for HIV in the British Isles: estimates based on surveillance data. Issue 7219 (6th November 1999) - Duong, Trinh; Ades, A E; Gibb, Diana M; Tookey, Pat A; Masters, Janet
Abstract: Objective: To estimate and interpret time trends in vertical transmission rates for HIV using data from national obstetric and paediatric surveillance registers. Design: Prospective study of HIV infected women reported through obstetric surveillance. HIV infection status of the child and onset of AIDS were reported through paediatric surveillance. Rates of vertical transmission and progression to AIDS rate were estimated by methods that take account of incomplete follow up of children with indeterminate infection status and delay in AIDS reporting. Setting: British Isles. Subjects: Pregnant women infected with HIV whose infection was diagnosed before delivery, and their babies. Main outcome measures: Mother to child transmission of infection and progression to AIDS in children. Results: By January 1999, 800 children born to diagnosed HIV infected women who had not breast fed had been reported. Vertical transmission rates rose to 19.6% (95% confidence interval 8.0% to 32.5%) in 1993 before falling to 2.2% (0% to 7.8%) in 1998. Between 1995 and 1998 use of antiretroviral treatment increased significantly each year, reaching 97% of live births in 1998. The rate of elective caesarean section remained constant, at around 40%, up to 1997 but increased to 62% in 1998. Caesarean section and antiretroviral treatment together were estimated to reduce risk of transmission from 31.6% (13.6% to 52.2%) to 4.2% (0.8% to 8.5%). The proportion of infected children developing AIDS in the first 6 months fell from 17.7% (6.8% to 30.8%) before 1994 to 7.2% (0% to 15.7%) after, coinciding with increased use of prophylaxis against Pneumocystis carinii pneumonia. Conclusions: In the British Isles both HIV related morbidity and vertical transmission are being reduced through increased use of interventions